"The Film Music of 2022-2023 by Armenian Composers (A. Berberyan, V. Sharafyan) Depicting the Fate of a Soviet Person under the Totalitarian Regime" - Yepremyan, Լիլիթ Կառլենի (Musical Armenia, 2024)
The article is based on the author's report at the presentation of the collection of articles by Armenian and German musicologists "Creating Ideologies on Purpose" (Yerevan, 2022), published with the assistance of the Konrad Adenauer Foundation. In the context of interdisciplinary research, film music is considered in the films of the last two years, shot in Armenia and devoted to topics that are still taboo in domestic cinematography, i.e. the life of Armenians under the conditions of the ideology of totalitarianism and the personality cult of Stalin. They served as the subject of analysis. "American" (2022, a full-length feature film directed by Michael Gurjian, composer: Andranik Berberyan) is about mass repressions faced by repatriated Armenians from abroad during the 1940s, killed or thrown into prisons, camps and exiles. "Three Graves of the Artist" (2023, a full-length documentary film, directed by Harutyun Khachatryan, composer: Vache Sharafyan), embarks on an empirical study spanning three decades exploring the theme of emigration and escape from the ideology of Soviet dictatorship, focusing on the example of the tragic fate of the artist Vahan Ananyan, whose ashes were simultaneously buried in three cities: Yerevan, Tallinn, Odessa.